HIV-1 integrase resistance associated mutations and the use of dolutegravir in Sub-Saharan Africa: A systematic review and meta-analysis. - Ezechiel Ngoufack Jagni Semengue; Maria Mercedes Santoro; Valantine Ngum Ndze; Aude Christelle Ka'e; Bouba Yagai; Alex Durand Nka; Beatrice Dambaya; Desiré Takou; Georges Teto; Lavinia Fabeni; Vittorio Colizzi; Carlo-Federico Perno; et al. (Public Library of Science (PLoS), 2022)
As sub-Saharan Africa (SSA) countries are transitioning to dolutegravir (DTG)-based ART, baseline data are required for optimal monitoring of therapeutic response. In this frame, we sought to generate up-to-date evidence on the use of integrase-strand transfer inhibitors (INSTI) and associated drug resistance mutations (DRMs) within SSA. In this systematic review and meta-analysis, we included randomized and non-randomized trials, cohort-studies, cross-sectional studies, and case-reports published on INSTI or integrase DRMs in SSA. We included studies of patients exposed to DTG, raltegravir (RAL) or elvitegravir (EVG). Primary outcomes were "the rate of virological control (VC:<50copies/ml)" and "the presence of DRMs" on INSTI-based regimens among patients in SSA. We synthesised extracted data using subgroup analysis, and random effect models were used where appropriate. Additional analyses were conducted to assess study heterogeneity. We identified 1,916 articles/citations through database searches, of which 26 were included in the analysis pertaining to 5,444 patients (mean age: 37±13 years), with 67.62% (3681/5444) female. Specifically, 46.15% (12/26) studies focused on DTG, 26.92% (7/26) on RAL, 23.08% (6/26) on both DTG and RAL, and 3.85% (1/26) on EVG. We found an increasing use of DTG overtime (0% before 2018 to 100% in 2021). Median treatment duration under INSTI-based regimens was 12 [9-36] months. Overall, the rate of VC was 88.51% [95%CI: 73.83-97.80] with DTG vs. 82.49% [95%CI: 55.76-99.45] and 96.55% [95%CI: 85.7-100.00] with RAL and EVG, respectively. In univariate analysis, VC with DTG-containing vs. other INSTI-regimens was significantly higher (OR = 1.44 [95%CI: 1.15-1.79], p = 0.0014). Among reported DRMs at failure, the only DTG resistance-mutations were G118R and R263K. In SSA, DTG presents a superiority effect in VC compared to other INSTIs. Nonetheless, the early detection of INSTI-DRMs calls for sentinel surveillance for a successful transition and a sustained efficacy of DTG in SSA. PROSPERO Registration Number: CRD42019122424.